The Effect of Vitamin E Supplementation in Ration Containing Manhadden Fish Oil and Kernel Palm Oil on Fertility, Hatchability and Hatch Weight of Native Chickenâs Eggs - Iriyanti, Ning; Zuprizal, Zuprizal; Yuwanta, T; Keman, S (ANIMAL PRODUCTION, 2007)
The aim of this research was to know the effect of vitamin E supplementation in the ration containing manhadden fish oil and kernel palm oil on fertility, hatchability and hatch weight of native chicken egg. The research was done in Experimental Sub-station Faculty of Animal Sciences UNSOED, Purwokerto. The experiment was conducted from April to November 2005. Material used in this experiment was 48 chicken females (pullets) of 22 weeks old which reared intensively up to 48 weeks old and 20 cockerels as semen sources for artificial insemination. A Completely Randomized Design with 6 replicates for each treatment was used. Rations were formulated as follow: R0 = Control / basal feed + Vitamin E 0 mg/kg in feed; R1 = basal feed + Vitamin E 10 mg/kg in feed; R2 = basal feed + Vitamin E 20 mg/kg in feed; R3 = basal feed + Vitamin E 30 mg/kg in feed. Results indicated that the used of vitamin E of 30 mg/kg in feed containing 5% manhadden fish oil and 5% kernel palm oil improved chicken fertility by 76.69% to 87.07%. However, treatments has no significant (P>0.05) effects on hatchability and hatch weight. (Animal Production 9(1): 36-39 (2007) Key Words : vitamin E, fertility, hatchability, hatch weight